2018
DOI: 10.1074/mcp.ra117.000474
|View full text |Cite
|
Sign up to set email alerts
|

Proteome Data Improves Protein Function Prediction in the Interactome of Helicobacter pylori

Abstract: Helicobacter pylori is a common pathogen that is estimated to infect half of the human population, causing several diseases such as duodenal ulcer. Despite one of the first pathogens to be sequenced, its proteome remains poorly characterised as about one third of its proteins have no functional annotation. Here, we integrate and analyze known protein interactions with proteomic and genomic data from different sources. We find that proteins with similar abundances tend to interact. Such an observation is accomp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 56 publications
0
10
0
Order By: Relevance
“…Interestingly, the expression of hp1076 is RpoN-dependent and its transcription level is found to be up-regulated together with flaB and flgE in a fliK mutant which displayed impaired motility and polyhook structures (Douillard et al, 2009). Recent interactome studies of H. pylori have further identified the binary complex of FliS-HP1076 and thus highlighting the potential functional significance of this heterodimer (Wuchty et al, 2018). Given that HP1076 is uniquely found in epsilon-proteobacteria and adopts a flagellinlike structure, it may play a specific role for the motility adaptation of this microbial species.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, the expression of hp1076 is RpoN-dependent and its transcription level is found to be up-regulated together with flaB and flgE in a fliK mutant which displayed impaired motility and polyhook structures (Douillard et al, 2009). Recent interactome studies of H. pylori have further identified the binary complex of FliS-HP1076 and thus highlighting the potential functional significance of this heterodimer (Wuchty et al, 2018). Given that HP1076 is uniquely found in epsilon-proteobacteria and adopts a flagellinlike structure, it may play a specific role for the motility adaptation of this microbial species.…”
Section: Discussionmentioning
confidence: 99%
“…Apart from the increased level of SpoT, proteomic studies by Wuchta et al [ 77 ] and Loke et al [ 78 ] showed an increase in the production of the following components in spherical H. pylori forms: outer membrane proteins (Omp7 (HopF), Omp8 (HopG), Omp11 (HorE), Omp15 (HopE), and Omp25 (HopI)), transporter proteins/efflux pumps, flagellin A, urease and hydrogenase subunits, proteins regulating the metal ions concentration (e.g., NikR being crucial for urease and hydrogenase activity [ 79 ]), CagE and CagV (stabilizing the T4SS pilus biogenesis [ 80 ]), VacA (related to cytotoxicity and immunosuppression induction [ 81 ]), lipoprotein LPP20 and TNF-α-inducing protein (both contributing to the carcinogenesis promotion [ 82 ]), as well as MreB (influencing the action of urease, hydrogenase, and VacA [ 83 ]).…”
Section: Phenotypic Variability As a Modulator Of H Pylmentioning
confidence: 99%
“…This is associated with the lack of a uniform procedure stimulating the transition of H. pylori from spiral to coccoid forms. Some reach teams use stressful conditions, such as nutritional starvation [ 43 ] or exposure to high oxygen concentrations [ 84 ], while others achieve this through a prolonged cultivation [ 77 , 78 ]. However, it cannot be denied that such procedures can independently affect the transcriptome and/or proteome of H. pylori cells.…”
Section: Phenotypic Variability As a Modulator Of H Pylmentioning
confidence: 99%
See 2 more Smart Citations